2017
DOI: 10.1038/s41598-017-03065-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing photoelectrochemical water oxidation, recombination kinetics and charge trapping in the three polymorphs of TiO2

Abstract: In this article we present the first comparative study of the transient decay dynamics of photo-generated charges for the three polymorphs of TiO2. To our knowledge, this is the first such study of the brookite phase of TiO2 over timescales relevant to the kinetics of water splitting. We find that the behavior of brookite, both in the dynamics of relaxation of photo-generated charges and in energetic distribution, is similar to the anatase phase of TiO2. Moreover, links between the rate of recombination of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 38 publications
8
43
0
Order By: Relevance
“…We should make it clear that this was not because holes in anatase cannot be scavenged strongly by methanol, indeed they can, where nanopowders or mesoporous structures often show a strong hole scavenging effect. 62,64,65 However, in the case of a flat and dense sample, the quantum yield of this interaction is too low to see a hole scavenging effect (as bulk electron-hole recombination dominates). 65 Overall, our TAS results show that the innate electron-hole recombination dynamics are similar in brookite and anatase, akin to previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…We should make it clear that this was not because holes in anatase cannot be scavenged strongly by methanol, indeed they can, where nanopowders or mesoporous structures often show a strong hole scavenging effect. 62,64,65 However, in the case of a flat and dense sample, the quantum yield of this interaction is too low to see a hole scavenging effect (as bulk electron-hole recombination dominates). 65 Overall, our TAS results show that the innate electron-hole recombination dynamics are similar in brookite and anatase, akin to previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…The decays appear linear on a log–log plot (Figure S12A, Supporting Information), indicating power‐law decay kinetics. At low fluences, the decays become more linear on a lin–log plot (Figure S12B, Supporting Information), potentially an indication of recombination of deeply trapped charges by tunneling . To gain more insight into the recombination mechanism, we attempted to fit the TAS decay dynamics by a model that considers first‐order monomolecular, second‐order bimolecular, and third‐order Auger processes (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, to the best of our knowledge, no theoretical study has been reported on electron trapping at the defects of brookite, even if similar results to anatase and rutile are expected. Some of the authors recently reported a study on trapped carriers in different TiO 2 polymorphs in the ms-s timescales, typical of photocatalytic reactions [58]. Also in these slow timescales, anatase and brookite exhibit dispersive power law recombination dynamics, in accordance with shallow charge trapping, while rutile exhibits logarithmic decay kinetics, indicative of deeper charge trapping.…”
Section: Photocatalytic Studiesmentioning
confidence: 95%
“…The density of such occupied mid-gap trap states (DOTS) can be studied by time-resolved vis-IR absorption spectroscopy (TRAS) [57,58]. In a recent experimental study, the depth of electron-traps in brookite was estimated to be 0.4 eV, which is deeper than that of anatase (<0.1 eV), but shallower than that of rutile (∼0.9 eV) [57].…”
Section: Photocatalytic Studiesmentioning
confidence: 99%